2012
DOI: 10.1128/mcb.05896-11
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Regulated MicroRNA MiR-181a Controls GluA2 Surface Expression in Hippocampal Neurons

Abstract: The dynamic expression of AMPA-type glutamate receptors (AMPA-R) at synapses is a key determinant of synaptic plasticity, including neuroadaptations to drugs of abuse. Recently, microRNAs (miRNAs) have emerged as important posttranscriptional regulators of synaptic plasticity, but whether they target glutamate receptors to mediate this effect is not known. Here we used microarray screening to identify miRNAs that regulate synaptic plasticity within the nucleus accumbens, a brain region critical to forming drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 68 publications
6
173
0
Order By: Relevance
“…miRNA-181a is rich in mature nerve cells and bioinformatic analysis has revealed that the cAMP response element-binding protein 1 (CREB1) mRNA 3'-UTR contains a complementary sequence to the miR-181a seed region. CREB1 is a key nuclear factor highly expressed in hippocampal neurons on which numerous signaling pathways converge (32)(33)(34). In the present study, the expression levels of these miRNAs were found to be significantly affected by sevoflurane and/or propofol anesthesia; therefore, general anesthesia may affect these cell signaling pathways, including synaptic plasticity and memory consolidation.…”
Section: Discussionmentioning
confidence: 49%
“…miRNA-181a is rich in mature nerve cells and bioinformatic analysis has revealed that the cAMP response element-binding protein 1 (CREB1) mRNA 3'-UTR contains a complementary sequence to the miR-181a seed region. CREB1 is a key nuclear factor highly expressed in hippocampal neurons on which numerous signaling pathways converge (32)(33)(34). In the present study, the expression levels of these miRNAs were found to be significantly affected by sevoflurane and/or propofol anesthesia; therefore, general anesthesia may affect these cell signaling pathways, including synaptic plasticity and memory consolidation.…”
Section: Discussionmentioning
confidence: 49%
“…MicroRNA activity can be modulated by altering the abundance of mature miRNA relative to target, for instance, through activity-dependent transcription, processing, and metabolism of miRNAs (Vo et al 2005;Kosik 2006;Impey et al 2010;Krol et al 2010;Wibrand et al 2010;Huang et al 2012;Saba et al 2012). This type of mechanism is well established in microRNA-mediated effects on neuronal differentiation or development.…”
Section: Differences Between Ca1 and Dgmentioning
confidence: 99%
“…These results suggest that (1) mGluR and NMDARs interact in the regulation of the miRNA transcription and biogenesis and (2) that some mature miRNAs are subject to NMDA receptordependent destabilization and decay. Recent studies have also demonstrated regulation of AMPA receptors by miR181a and mir181b (Saba et al 2012). The control of miRNA-124 function by neurotransmitter serotonin in Aplysia and relief of miR-134-mediated repression of LimK1 by BDNF are classic examples of regulation of miRNA function upon neuronal activity (Schratt et al 2006;Rajasethupathy et al 2009).…”
Section: Differences Between Ca1 and Dgmentioning
confidence: 99%
“…Whereas accumulating evidence indicates that phosphorylation and trafficking play important roles in regulation of glutamate receptor signaling, the molecular mechanisms regulating glutamate receptor expression levels remain unexplored. Recent work suggests that the miRNA pathway regulates the AMPAR subunit GluR2 expression (9,10). In hippocampal neurons, MiR-125b has been shown to regulate the NMDAR subunit NR2A (11).…”
mentioning
confidence: 99%